2014
DOI: 10.1097/qad.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Viral load versus CD4+ monitoring and 5-year outcomes of antiretroviral therapy in HIV-positive children in Southern Africa

Abstract: Objectives Many paediatric antiretroviral therapy (ART) programmes in Southern Africa rely on CD4 counts to monitor ART. We assessed the benefit of replacing CD4 by viral load (VL) monitoring. Design Mathematical modelling study. Methods Simulation model of HIV progression over 5 years in children on ART, parameterised by data from seven South African cohorts. We simulated treatment programmes with 6-monthly CD4 count or 6- or 12-monthly VL monitoring. We compared mortality, second-line ART use, immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…A large proportion of the children who have started with a standard NNRTI-based regimen may need second-line ART in adolescence. 13,23 The current recommendations suggest that children <3 years should start with a PI-based first line regimen 2 , making it complicated to find suitable and affordable regimens for those patients who experience treatment failure. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large proportion of the children who have started with a standard NNRTI-based regimen may need second-line ART in adolescence. 13,23 The current recommendations suggest that children <3 years should start with a PI-based first line regimen 2 , making it complicated to find suitable and affordable regimens for those patients who experience treatment failure. 10 …”
Section: Discussionmentioning
confidence: 99%
“…12 The structure is similar to models we have developed before, 10,11,13 and a detailed description is given in the Supplementary Appendix, Text S1. We simulated cohorts of 10,000 adults (>15 years) who progress from ART initiation through a sequence of health states that combine the patient’s virological, immunological, clinical and retention status and the type of treatment regimen (first- or second-line) (Supplementary Appendix, Text S1, Table S1.1).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to poor viral suppression with ART, infants generally have better immune status on ART than older children[1719]; this may be due to their high thymic output[20] and higher age-specific CD4 counts and CD4%[2123], or to greater damage to the CD4 T-cell population among older children who have lived with untreated HIV for an extended period[2425]. As ART response is primarily assessed using CD4 monitoring in developing country settings[2629], treatment failure among infants in particular may be masked by their comparatively good CD4 counts and percentages[26,29,30]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that absence of virological monitoring and a delayed switch of therapy lead to a high degree of accumulation of DRMs [22] and an increased mortality [23]. Since 2013, WHO have included virological testing as the preferred monitoring strategy [10], which may eventually enable affordable viral load testing in resource-limited settings and shift the cost/benefit balance in favour of implementing virological monitoring on a broader scale.…”
Section: Discussionmentioning
confidence: 99%